The role of personality on resilience-moderated work stress in employees - Hasudungan, Gerald Nicholas; Mustika, Martina Dwi (Jurnal Ilmiah Psikologi Terapan, 2024)
The COVID-19 pandemic has had an impact on the entire business industry. Various companies are facing the post-pandemic situation and are trying to make adjustments to the current situation. The adjustments made by these companies create an impact on employees and lead to work stress for them. This study aims to examine the moderating effect of resilience on the relationship between personality and employee work stress. The results of previous research found inconsistencies in the results of the correlation between personality and employee work stress. Resilience, which can buffer the effects of work stress, is used as a moderating variable. The number of respondents who were actively involved was 499, who were employees aged 22–40 years and worked in various business sectors. All respondents have filled out three measurement scales: the personality scale, the work stress scale, and the resilience scale. Data collection was carried out using Google Forms. This study conducted a moderation analysis using the Hayes model 1 macro process to test the research model. Study findings show that the role of resilience moderates the relationship between personality and employee work stress (p = 0.003). The findings also show that resilience will be able to reduce work stress felt by individuals. Resilience is a component that can protect individuals from the impact of work stress. Companies need to provide assistance to improve their employees' resilience skills to reduce the daily effects of work stress.